Family Factors and the Psychological Well-Being of Children and Adolescents with Inflammatory Bowel Disease—An Exploratory Study - Chantal Hieronymi; Kalina Kaul; Jan de Laffolie; Burkhard Brosig; on behalf of Cedata-GPGE AG (Children)
Background/Objectives: The aim of our study was to examine the influence of family structure and the number of siblings on psychological problems and illness-related emotions in children and adolescents with inflammatory bowel disease (IBD) and the relationship between emotional coping in children and parents. Methods: CEDNA is a nationwide German online and paper-based questionnaire administered between October 2021 and April 2022. Adolescents with IBD, aged 12 to 17 years, and parents of children aged 0 to 17 years with diagnosed IBD, were included. SAS was used for descriptive statistics and logistic regression analysis was performed using R Studio (PBC; 2023.06.0 + 421). Results: 1158 participants (450 adolescents and 708 parents) were included in the study. A two-parent household could not be associated with mental illness as a comorbidity in pediatric IBD patients (p = 0.06) but was shown to decrease the risk of sadness (p < 0.001), helplessness (p < 0.01), feeling left alone and lonely (p < 0.05). A single-parent household increased the risk of sadness (p = 0.001), helplessness (p = 0.002), and loneliness (p = 0.006). Having one to two siblings was associated with a lower risk of mental health problems (p = 0.03) and reduced anxiety (p = 0.005). An association was also found between parents and children’s emotional coping skills. Conclusions: Further research on family structure and siblings in pediatric IBD is needed, given the potential impact on children’s psychological well-being.